2013
DOI: 10.1039/c2tb00061j
|View full text |Cite
|
Sign up to set email alerts
|

Calcium phosphate-based cements: clinical needs and recent progress

Abstract: Although autografts are considered to be the current gold standard, there is still clinical demand for synthetic bone graft substitutes. Calcium phosphate cements (CPCs) have many favourable properties that support their clinical use in the repair of bone defects. Although the translation of CPCs from the bench to the bedside has been quite successful, some issues remain. This review article provides an overview of the recent progress in the development of CPC-based materials and also emphasises the challenges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
91
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 105 publications
0
91
0
Order By: Relevance
“…In the design of scaffolds for bone tissue engineering, appropriate degradability is an important factor that must be taken into account. 29 In this study, it is found that the weight loss of all the scaffolds increased as a function of soaking time.…”
Section: Discussionmentioning
confidence: 84%
“…In the design of scaffolds for bone tissue engineering, appropriate degradability is an important factor that must be taken into account. 29 In this study, it is found that the weight loss of all the scaffolds increased as a function of soaking time.…”
Section: Discussionmentioning
confidence: 84%
“…CPC has been used for synthetic bone grafts in bone engineering because of its excellent bioactivity and osteoconductivity25262728. Li/CPC was manufactured by doping lithium chloride onto CPC.…”
Section: Discussionmentioning
confidence: 99%
“…Various growth factors and mesenchymal cells reside in the sample surfaces or surrounding the implants [6]. The quantitative experimental findings were confirmed after Western blotting assessment of ROI.…”
Section: Discussionmentioning
confidence: 87%